2018
DOI: 10.1186/s13104-018-3550-z
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent deliveries in rural Cameroon: comparison of delivery outcomes between primipara and multipara adolescents

Abstract: ObjectiveAdolescent pregnancies are high risk and deliveries in this age group are usually associated with adverse outcomes. The perception that multiparous adolescents have better delivery outcomes than primiparous counterparts is not uncommon. We sought to determine if multiparous adolescents were precluded from having adverse delivery outcomes when compared to primiparous adolescents. The data used for the analysis is a side product from a published project aimed at mapping the epidemiology of adolescent de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…Adolescent pregnancies are said to be significantly associated with adverse maternal and neonatal outcomes [35][36][37]40]. However, in our findings, consistent with results from studies conducted in Nigeria and six other LMICs [6,32], adolescence generally did not have a statistically significant association with poor maternal outcomes.…”
Section: Discussionsupporting
confidence: 83%
“…Adolescent pregnancies are said to be significantly associated with adverse maternal and neonatal outcomes [35][36][37]40]. However, in our findings, consistent with results from studies conducted in Nigeria and six other LMICs [6,32], adolescence generally did not have a statistically significant association with poor maternal outcomes.…”
Section: Discussionsupporting
confidence: 83%
“…In this review, adolescents presenting for delivery were just as likely to be married as adult women. In most rural areas and some regions like the Far north of the country, adolescent marriages are common practice [1,8,10,12]. This could explain why the proportions of married adolescents presenting for deliveries was similar to that of married adult women.…”
Section: Discussionmentioning
confidence: 99%
“…Adolescent deliveries carry a high risk of adverse outcomes to both the mother and the baby largely due to a biological and physiological immaturity; particularly pelvic and perineal immaturity in adolescents [1][2][3]. Some of the adverse outcomes of adolescent deliveries to the mother include: a higher rate of caesarean sections, perineal trauma and maternal death; while neonates born to adolescent mothers are likely to suffer from asphyxia, low birth weight and neonatal death [1,[4][5][6][7][8][9][10]. The mortality associated with adolescent deliveries and the long-term morbidity due to its adverse outcomes like low birth weight (which has a known relationship with neurodevelopmental complications) [11], makes adolescent births a public health issue.…”
Section: Introductionmentioning
confidence: 99%
“…The mean primiparity age was 18.01 years ± 3.52. In a publication on adolescent childbirth in Cameroon, Njim et al identified a similar mean age, 17.8 years ± 1.3 [7]. However, this is much lower than the mean age of primiparity of 30.8 ± 5.2 years reported in a study done in Chile on the prevalence of anal sphincter lesions after childbirth [2].…”
Section: Discussionmentioning
confidence: 82%
“…Studies in some Cameroonian semi-rural settings have suggested that being a primiparous adolescent woman increases the likelihood of having a low birth weight neonate compared to their multiparous counterparts [7]. Another study revealed that primiparous women aged 27 years and above have a significantly increased risk of cesarean section, instrumental delivery and poor neonatal outcome [8].…”
Section: Introductionmentioning
confidence: 99%